ANALISIS KEMANDIRIAN BELAJAR PESERTA DIDIK SEKOLAH DASAR - Arifin, Nurdin; Tihin, Angela Merici (SISTEMA: Jurnal Pendidikan, 2024)
This research was motivated because there were students who were less independent in learning at SD Negeri 020 North Samarinda such as lack of discipline in learning, where sometimes students were noisy and did not listen to material explanations from when studying in class, lack of confidence and lack of sense of responsibility to complete tasks. Research is useful in describing the learning independence of grade V students at SD Negeri 020 North Samarinda for the 2022/202 learning year. Subject collection techniques apply purposive sampling and data analysis starting from the process of collecting data, determining data, presenting data, and formulating conclusions. The type of triangulation used is source triangulation. The results revealed that the independence of students in learning in grade V SD Negeri 020 North Samarinda developed quite well and was classified as quite good, where students already had independence and applied independence in the learning process both in the school and home environment on 5 indicators of student learning independence, namely confidence, responsibility, discipline in learning, motivation in learning as well as being active.